A survey of attitudes of patients in a department of genitourinary medicine. Issue 3 (June 1978) - Balsdon, M J; Charlton, B; Curran, M; Singha, H S
Abstract : A questionnaire concerning clinic organisation was completed by 415 patients attending a department of genitourinary medicine. Most (62.9%) patients preferred to be identified by number rather than by name, and about half (52.7%) did not like mixed waiting rooms. An appointment system as well as having an open clinic was liked by twice as many (44.9%) as those patients (23.6%) against such a system. More information about sexually transmitted diseases in the form of leaflets, etc. at the clinic was requested by most (79.1%) patients and a similar number (82.0%) felt the department itself should be more widely advertised.